The Therapeutic Potential of Small Pharmacological Molecules in the Treatment of Sialidosis - O`Leary, Erin M. (My University, 2010)
Sialidosis is an autosomal recessive disorder caused by a dysfunctional Sialidase enzyme. Categorized into two phenotypes. Sialidosis type I and II. Sialidosis is a highly heterogeneous disorder with varying ages of onset and pathologies. Currently, there is no viable therapy for the treatment of Sialidosis patients. At the molecular level, cells from Sialidosis patients with compound heterozygous mutations show improper enzyme folding, loss of Sialidase enzyme activity and subsequent accumulation of sialylconjugates within lysosomes. One promising treatment option is the use of small pharmacological molecules as immune response. and proteasome regulators. In this study. We examined the efficacy of the immuno-suppressant (Celastrol) as well as a proteasomal inhibitor (MG132) in the rescue of mutant enzymes with altered conformation. Our results reveal that MG132 is highly beneficial to enzyme activity. localization and substrate reduction in cells expressing defective Sialidase. We also found that MG132 reduces accumulation of ganglioside products. GT1b, GD3, and GM3 in pre-loaded Sialidosis cells. Alternatively, Celastrol appears to inhibit; if not deplete Sialidase expression and activity revealing a potentially novel effect of Celastrol on immune modulators. Of interest. the combination of Celastrol and MG132 appears to
amplify the beneficial impact of MG132 across most of the molecular analysis of both the endogenous and recombinant expression of defective Sialidase. This study explores a novel biological criteria to assess the efficacy of small molecules through substrate accumulation analysis and points to a potential therapeutic strategy for the treatment of Sialidosis.
Keywords: Biology; Biology; Biology